Academic discourse and global publishing : disciplinary persuasion in changing times - Hyland, Ken; Jiang, Feng (Kevin) (Routledge, 2019)
Academic Discourse and Global Publishing offers a coherent argument for changes in published academic writing over the past 50 years. Demonstrating how published writing represents academics' decisions about how best to present their work, their readers and themselves in the global context of a rapidly shifting university system, this book provides: An up-to-date reference on contemporary topics in specialist discourse analysis, current research methodologies and innovative approaches to the study of writing; New insights into conceptual and theoretical issues related to the analysis of academic writing; An accessible introduction to diachronic research in EAP and a case for the value of the diachronic study of texts using corpus techniques; A clear overview of how texts work in interaction and how they relate to evolving institutional and political contexts; Links between the practices of different disciplines and the environments in which they operate, as well as observations on the ways in which they differ. This volume is essential reading for students and researchers of EAP/ESP and Applied Linguistics and will also be of significant interest to academics and students looking to have their work published.- Resumé vydavatel